Family as the Institute of Private Law and the Essential Factor of Public Law Integrity - Arlauskas, Saulius (Socialinė teorija, empirija, politika ir praktika, 2017)
In light of the theoretical meaning attributed to the correlation of public and private law, the article is seeking to consider social moral statements on the legal regulation of the institution of family. There is an incorrectly interpreted and therefore criticized thesis that describes the legal neutrality of the State, on the basis of which the creation of a family is an absolutely autonomic matter of two private subjects; as a result, the State cannot dictate any ideal model of the family. In this study, it is proved that such position is based on an uncritical comprehension of the difference between Law and Morality and the rejection of their common universal values. In the article, it is argued that the liberal doctrine of Law based on social collective ethic statements is unavoidably presumed as the imperative of public Law, of the unavoidably unique nature of an individual and also his rights for equality and freedom of choice. This way, it is demonstrated that the competence of private Law to protect free agreements of individuals is achieved not by their individual disposition, but by the collective being of the society. By taking into account the common origins of freedom and the equality of a society’s members, the main procreative function of the family institution is considered, a function which is also required by the community’s identity as a striving of the society for survival in history. It is shown that the state, as it patronizes different-sex marriages, does not simultaneously neglect an individual’s freedom of choice, but, on the contrary, the freedom of choice receives meaningful content that follows the common universal values for both Law and Morality. This article claims that the wish to weaken the social importance of traditional family is dangerous, since it fractures the main source of social integration models – the traditional family.